Trait pour Trait : 50 autoportraits. (Paris : Galerie Jean Briance, 1976)
Andrea, Pat ; Arroyo, Eduardo ; Arikha, Avigdor ; Buri, Samuel ; Bellmer, Hans ; Blokhuis, Peter ; Bennett, John ; Dierickx, Karel ; Dine, Jim ; Csernus, Tibor ; Diaz, Gérard ; Governatori, Aroldo ; Gasiorowski, Gérard ; Hermann, Claude ; Gironella, Alberto ; Helion, Jean ; etc.
Trait pour Trait : 50 autoportraits, Galerie Jean Briance, Paris, 11 mars - 30 avril 1976
boek